Two-component adhesive as well as preparation method and application thereof

By making a crosslinker in the adhesive and adopting a two-component structure, the problems of insufficient anti-aging performance and inconsistent bonding strength of the existing adhesives in high temperature and high humidity environments are solved, and efficient and environmentally friendly bonding effect is achieved.

CN119391343AActive Publication Date: 2025-02-07WANHUA CHEM GRP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411487075.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-07
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The existing adhesives have insufficient anti-aging performance in high temperature and high humidity environments, inconsistent adhesive strength, and contain environmentally-constrained components, which limits their application range.

Method used

By using the preparation method of a two-component adhesive, a high-element adhesive is prepared by making a home-based crosslinking agent, a small molecular weight polyether and isocyanate reaction is used to introduce alcohol or amine containing tertiary amines, and blocked with monoaminosiloxane to form an efficient adhesive.

Benefits of technology

A two-component adhesive with good bond strength consistency under different temperature and humidity conditions has good anti-aging properties and environmental protection, and is free of solvents and environmentally friendly components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005098995090000011
    Figure BDA0005098995090000011
  • Figure BDA0005098995090000041
    Figure BDA0005098995090000041
  • Figure BDA0005098995090000051
    Figure BDA0005098995090000051
Patent Text Reader

Abstract

The invention provides a two-component adhesive as well as a preparation method and application thereof. The double-component adhesive disclosed by the invention comprises a component A and a component B which are independent, the component A comprises silane modified polyether, an epoxy curing agent, a modified cross-linking agent, a coupling agent, an auxiliary agent, a filler and a dewatering agent; and the component B comprises epoxy resin, a filler and a catalyst. The double-component adhesive disclosed by the invention has better elongation at break and higher bonding strength, is not strong in dependence on a use environment, is good in curing and bonding strength consistency under different temperature and humidity conditions, does not need prime coat, has good bonding force on various materials such as conventional metal, engineering construction profiles, thermoplastic materials and glass, is moderate in viscosity, and can be applied to the field of adhesive materials. The high-temperature-resistant and anti-sagging coating has the advantages of high temperature resistance, sagging resistance, fast strength establishment, good anti-aging performance under various severe conditions of high temperature, high humidity and the like, no solvent, no butyltin, no octyltin, no phenyltin and other environment-friendly limited components, and meeting of the environment-friendly requirement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of adhesives, and in particular relates to a two-component adhesive and a preparation method and application thereof. Background Art

[0002] As a multifunctional, high-performance adhesive, structural adhesive plays a key role in many fields such as construction, manufacturing, and transportation engineering. MS adhesive is similar to a combination of silicone adhesive and PU adhesive. It has the excellent elastic elongation of silicone adhesive and good weather resistance, but its bonding strength is relatively small. Acrylate structural adhesive is a type of adhesive based on acrylate monomers. It has the characteristics of rapid curing, strong adhesion and high transparency, but its monomers have odor, toxicity and flammability, which may cause stress cracking on some plastic substrates. The bonding surface needs to add a primer, which limits its application. Epoxy structural adhesive has excellent adhesion, corrosion resistance and high temperature stability, but poor toughness, easy yellowing and low elongation. Polyurethane structural adhesive has high strength, simple use process and easy bonding. It does not require special surface treatment of the bonded surface. It can be cured at room temperature or heat cured. It will release heat during curing, but its biggest disadvantage is that it has poor resistance to high temperature and humidity, and relatively weak corrosion resistance. The ever-growing demand, the diversification of substrates, the differences in downstream processes and environments, and the changing external environment in which finished products are used have led to increasingly higher requirements for adhesives, and it is difficult for a single type of adhesive to meet the requirements.

[0003] Patent CN117126633A discloses an epoxy resin-silane terminated resin two-component hybrid structural adhesive and its preparation method and application. Components A and B are prepared using silane terminated resin and epoxy resin, and are used in electronic display screens and new energy vehicles. The two components are simply physically blended after mixing, and the bonding between the two phases is poor, so it is necessary to ensure reworkability. The final tested bonding strength is not high. Organic tin is used as a catalyst, which does not meet environmental protection requirements. Adding plasticizers poses a risk of migration or precipitation. Summary of the invention

[0004] In view of the existing problems, the purpose of the present invention is to provide a two-component adhesive, a preparation method and an application thereof. The two-component adhesive has good elongation at break and high bonding strength, is not strongly dependent on the use environment, has good consistency in cured bonding strength under different temperature and humidity conditions, does not require a primer, has good bonding force to a variety of materials such as conventional metals, engineering construction profiles, thermoplastic materials, glass, etc., has moderate viscosity, is anti-sagging, and has fast strength building. It exhibits good anti-aging performance under a variety of harsh conditions such as high temperature and high humidity, does not contain solvents, does not contain environmentally restricted components such as butyl tin, octyl tin, and phenyl tin, and meets environmental protection requirements.

[0005] In order to achieve the above object, the technical solution of the present invention is as follows:

[0006] A two-component adhesive, the adhesive consisting of component A and component B;

[0007] The A component comprises the following components in parts by weight:

[0008]

[0009]

[0010] The B component includes the following components in parts by weight:

[0011] Epoxy resin 90-95 parts

[0012] Filler 1-5 parts The mixing mass ratio of the catalyst 1-5 parts A component and the B component is 1:1 to 3:1.

[0013] In the present invention, the silane-modified polyether in the component A is a dimethoxy-terminated silane-modified polyether and a trimethoxy-terminated silane-modified polyether, which is selected from one or more of SAX750, SAX260, SAX590, Wacker Chemical E35, Wacker Chemical E10, Ruiyang Antai 350A, and Xinda Chemical M3001.

[0014] In the present invention, the epoxy curing agent in component A is selected from at least one of aliphatic amines, aromatic amines, aliphatic rings, modified amines, tertiary amines, acid anhydrides, low molecular weight polyamides and latent amines, and is selected from one or more of (1,3-cyclohexanedimethylamine) alicyclic amine, diethylenetriamine, isophoronediamine, 2,4,6-tris(dimethylaminomethyl)phenol and benzyldimethylamine.

[0015] The modified crosslinking agent is prepared by reacting low number average molecular weight polypropylene oxide alcohol and / or polyethylene oxide alcohol with alcohol or amine containing tertiary amine groups and monoaminosiloxane with isocyanate. The specific preparation method comprises the following steps:

[0016] Place isocyanate and polyol in a reactor, add a catalyst and react at 65-75°C for 2-3 hours, test the isocyanate content of the reaction, when the isocyanate content reaches the theoretical value, add an alcohol or amine containing a tertiary amine group and react at 60-65°C for 1-2 hours, when the isocyanate content reaches the theoretical value, cool to 30-40°C, add monoaminosiloxane and react for 1-2 hours, when the isocyanate content reaches the theoretical value, cool to obtain a modified cross-linking agent.

[0017] In the present invention, the isocyanate is selected from one or more of diphenylmethane diisocyanate, hexamethylene diisocyanate, dicyclohexylmethane diisocyanate and isophorone diisocyanate.

[0018] The alcohol or amine containing a tertiary amine group is one or more of N-methyldiethanolamine, dimethyldipropylenetriamine, and N,N-bis(3-aminopropyl)methylamine.

[0019] The polyol is polypropylene oxide alcohol and / or polyethylene oxide alcohol; for example, polypropylene oxide diol or triol and / or polyethylene oxide diol or triol alcohol with a number average molecular weight of 400-1000, selected from one or more of Wanhua Chemical C2004, C2010D, C2010A, R2303, and R2304.

[0020] The monoaminosiloxane is one or more of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, and 3-aminopropylmethyldiethoxysilane.

[0021] The catalyst is bismuth neodecanoate or zinc isooctanoate.

[0022] In the present invention, the mass ratio of the isocyanate, the polyol, the alcohol or amine containing a tertiary amine group, and the monoaminosiloxane is (45-70): (40-55): (9-14): (25-37).

[0023] In the present invention, the coupling agent is at least one of an amine-containing coupling agent and an epoxy-containing coupling agent, such as 3-aminopropyltriethoxysilane KH550, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane KH792, and 3-(2,3-epoxypropoxy)propyltrimethoxysilane Z6040.

[0024] In the present invention, the filler is at least one selected from calcium carbonate, talc, quartz powder, mica powder, titanium dioxide, fumed silica, bentonite, carbon black, aluminum hydroxide and aluminum oxide.

[0025] In the present invention, the dehydrating agent is vinyl silane, such as at least one of vinyl trimethoxy silane, vinyl triethoxy silane and vinyl tri(methoxyethoxy) silane.

[0026] In the present invention, the auxiliary agent is one or more of an ultraviolet light absorber, a hindered amine light stabilizer and an antioxidant having a light stabilizing effect, such as Tinuvin B75 and Tinuvin B88 produced by BASF of Germany, and Shanghai Puzhan U5068.

[0027] In the present invention, the epoxy resin is a bisphenol A type epoxy resin, such as Baling Petrochemical Epoxy Resin E51 and E44.

[0028] In the present invention, the catalyst is a composite catalyst, such as Jianyi Chemical Catalyst KAT245.

[0029] On the other hand, the present invention also provides a method for preparing a two-component adhesive, comprising the following steps:

[0030] (1) Preparation of component A: silane-modified polyether and filler are mixed and dehydrated at 90-120° C. and vacuum degree of -0.06 to -0.1 MPa for 1-2 h, cooled to below 30° C., epoxy curing agent, modified cross-linking agent, coupling agent, auxiliary agent, and dehydrating agent are added, and stirred at vacuum degree of -0.06 to -0.1 MPa for 0.5 to 1 h to obtain component A;

[0031] (2) Preparation of component B: The modified epoxy resin and filler are mixed and dehydrated at 90-120°C and vacuum degree -0.06 to -0.1 MPa for 1-2 hours, cooled to below 30°C, and a catalyst is added.

[0032] Stir at -0.1MPa for 0.5 to 1h to obtain component B.

[0033] (3) Mix component A and component B in a ratio of 1:1 to 3:1.

[0034] Finally, the present invention provides an application of a two-component adhesive in bonding materials, wherein the bonding materials include aluminum, stainless steel, galvanized sheet, glass, PVC, PC, ABS, etc.

[0035] Compared with the prior art, the beneficial effects of the technical solution of the present invention are:

[0036] The invention adopts a self-made cross-linking agent, adopts a small molecular weight polyether and an isocyanate to react, further introduces an alcohol or amine containing a tertiary amine, and finally uses a monoaminosilane for end-capping. The obtained cross-linking agent has a small molecular weight, has more carbamate bonds and urea bonds on the overall chain segment, has a strong force with the substrate, and forms good adhesion. At the same time, the tertiary amine in the chain segment can react with the epoxy group to connect the two phases to form a whole. The physical winding force is stronger than that of the individual phases, and the aging resistance is excellent, so that the obtained two-component adhesive has good elongation at break and high bonding strength, is not strongly dependent on the use environment, has good consistency in cured bonding strength under different temperature and humidity conditions, does not require a primer, has good adhesion to various materials such as conventional metals, engineering construction profiles, thermoplastic materials, glass, etc., has moderate viscosity, is anti-sagging, has fast strength building, exhibits good anti-aging performance under various adverse conditions such as high temperature and high humidity, does not contain solvents, adopts a composite catalyst, does not contain environmentally restricted components such as butyltin, octyltin, phenyltin, etc., and meets environmental protection requirements. DETAILED DESCRIPTION

[0037] Raw materials and sources

[0038] Silane modified polyether M3001, (Shanghai Xinda Chemical Co., Ltd., industrial grade)

[0039] Dimethyldipropylenetriamine (Xindian Chemical Materials (Shanghai) Co., Ltd., analytical grade)

[0040] N'N-Bis(3-aminopropyl)methylamine (Aladdin, industrial grade)

[0041] Polyether polyol C2004 (Wanhua Chemical Group Co., Ltd., industrial grade)

[0042] Polyether polyol C2010D (Wanhua Chemical Group Co., Ltd., industrial grade)

[0043] Polyether polyol R2305 (Wanhua Chemical Group Co., Ltd., industrial grade)

[0044] Polyether polyol C2020 (Wanhua Chemical Group Co., Ltd., industrial grade)

[0045] HMDI (dicyclohexylmethane diisocyanate, Wanhua Chemical Group Co., Ltd., industrial grade)

[0046] BDO (1,4-Butanediol, Bailingwei Technology Co., Ltd., industrial grade)

[0047] IPDI (isophorone diisocyanate, Wanhua Chemical Group Co., Ltd., industrial grade)

[0048] HDI (hexamethylene diisocyanate, Wanhua Chemical Group Co., Ltd., industrial grade)

[0049] Bismuth neodecanoate (American leading chemical company, analytical grade)

[0050] 3-Aminopropyltriethoxysilane KH550 (Shanghai Aladdin Biochemical Technology Co., Ltd., industrial grade)

[0051] 3-Aminopropyltrimethoxysilane SICO-A111 (Silicon Science, industrial grade)

[0052] 3-(2,3-Epoxypropyl)propyltrimethoxysilane Z6040 (Dow Corning, industrial grade)

[0053] U-5068 (Shanghai Puzhan Industrial Co., Ltd., industrial grade)

[0054] 2,4,6-Tris(dimethylaminomethyl)phenol DMP-30 (Shanghai Jizhi Biochemical Technology Co., Ltd., industrial grade)

[0055] Filler: Fumed silica R202 (Evonik, industrial grade)

[0056] Vinyltrimethoxysilane A171 (Momentive, industrial grade)

[0057] Epoxy resin E51 (Sinopec Baling Petrochemical, industrial grade)

[0058] Catalyst KAT245 (Jianyi Chemical, industrial grade)

[0059] <Test Method>

[0060] Tensile strength and elongation at break test: Tested in accordance with GB / T 528.

[0061] Shear strength test: refer to GB / T7124 tensile shear strength test method, all substrates are not treated before bonding.

[0062] Aging performance: Put the cured colloid into a hot and humid chamber at a temperature of 85±2℃ and a humidity of 85±5% for 15 days, and then test the tensile properties of the colloid and the shear properties of different substrates.

[0063] Shear strength test under different temperature and humidity conditions: Shear strength was tested after storage under condition A: 25°C, 50% RH for 7 days, condition B: 5°C, 30% RH for 7 days, and condition C: 40°C, 70% RH for 7 days.

[0064] Curing speed test: Under the conditions of 25°C and 50% RH, AL+AL substrate was selected and the shear strength was tested after curing for 1h, 1d, 3d, 5d and 7d respectively.

[0065] Example 1

[0066] Preparation of modified cross-linking agent:

[0067] Put 69g HMDI and 52g C2004 in a four-necked flask, add 0.02g bismuth neodecanoate as catalyst, react at 65℃ for 2h, test the isocyanate content and it is 9.23%, which is lower than the theoretical value of 9.25%, add 9g dimethyldipropylenetriamine and react at 60℃ for 1h, test the isocyanate content and it is 4.93%, which is lower than the theoretical value of 4.96%, cool to 40℃, add 34.02g KH550 and react for 1.5h, test the isocyanate content and it is 0.03%, cool to below 20℃ and seal for storage.

[0068] Preparation of adhesive component A, the raw material ratio is as follows:

[0069] Table 1 Example 1 Component A Raw Material Ratio

[0070]

[0071]

[0072] Process steps:

[0073] The silane modified polyether and filler are mixed and dehydrated at 120°C and a vacuum degree of -0.1 MPa for 2 hours, and the temperature is lowered to below 30°C. An epoxy curing agent, a modified cross-linking agent, a coupling agent, an auxiliary agent, and a dehydrating agent are added and stirred at a vacuum degree of -0.06 to -0.1 MPa for 0.5 to 1 hour to obtain component A.

[0074] Preparation of adhesive component B, the raw material ratio is as follows:

[0075] Table 2 Example 1 Component B Raw Material Ratio

[0076] raw material Brand or name Dosage (portion) Epoxy resin E51 90 filler R202 5 catalyst KAT245 5

[0077] Process steps:

[0078] The modified epoxy resin and filler were mixed and dehydrated at 120°C and a vacuum degree of -0.1 MPa for 2 hours, cooled to below 30°C, a catalyst was added, and stirred at a vacuum degree of -0.1 MPa for 1 hour to obtain component B.

[0079] Example 2

[0080] Preparation of modified cross-linking agent:

[0081] Put 50gHMDI and 52gC2010D in a four-necked flask, add 0.02g bismuth neodecanoate as catalyst, react at 65℃ for 2h, test the isocyanate content and it is 11.4%, which is lower than the theoretical value of 11.43%. Add 9g dimethyldipropylenetriamine and react at 60℃ for 1h, test the isocyanate content and it is 6.2%, which is lower than the theoretical value of 6.23%. Cool to 40℃, add 36.45gKH550 and react for 1.5h. Test the isocyanate content and it is 0.02%. Cool to below 20℃ and seal for storage.

[0082] Preparation of adhesive component A, the raw material ratio is as follows:

[0083] Table 3 Example 2 Component A Raw Material Ratio

[0084] raw material Brand or name Dosage (portion) Silane modified polyether M3001 87 Epoxy Curing Agent DMP-30 2 Modified crosslinking agent Modified crosslinking agent 5 Coupling agent Z6040 1 Additives U-5068 1 filler R202 3 Dewatering agent A171 1

[0085] Process steps: same as Example 1

[0086] Preparation of adhesive component B, the raw material ratio is as follows:

[0087] Table 4 Example 2 Component B Raw Material Ratio

[0088] raw material Brand or name Dosage (portion) Epoxy resin E51 95 filler R202 1 catalyst KAT245 1

[0089] Process steps: same as Example 1

[0090] Example 3

[0091] Preparation of modified crosslinking agent:

[0092] Put 55g IPDI and 52g C2040 in a four-necked flask, add 0.02g bismuth neodecanoate as catalyst, react at 65℃ for 2h, test the isocyanate content and it is 9.19%, which is lower than the theoretical value of 9.24%. Add 9g dimethyldipropylenetriamine and react at 60℃ for 1h. Test the isocyanate content and it is 4.4%, which is lower than the theoretical value of 4.43%. Cool to 40℃, add 27.11g KH550 and react for 1.5h. Test the isocyanate content and it is 0.02%. Cool to below 20℃ and seal for storage.

[0093] Preparation of adhesive component A, the raw material ratio is as follows:

[0094] Table 5 Example 3 Component A Raw Material Ratio

[0095] raw material Brand or name Dosage (portion) Silane modified polyether M3001 73 Epoxy Curing Agent DMP-30 6 Modified crosslinking agent Modified crosslinking agent 10 Coupling agent Z6040 2.5 Additives U-5068 2 filler R202 6.5 Dewatering agent A171 1.5

[0096] Process steps: same as Example 1

[0097] Preparation of adhesive component B, the raw material ratio is as follows:

[0098] Table 6 Example 3 Component B Raw Material Ratio

[0099] raw material Brand or name Dosage (portion) Epoxy resin E51 93 filler R202 2.5 catalyst KAT245 2.5

[0100] Process steps: same as Example 1

[0101] Example 4

[0102] Preparation of modified cross-linking agent:

[0103] Put 48gHDI and 52gR2305 in a four-necked flask, add 0.02g bismuth neodecanoate as catalyst, react at 65℃ for 2h, test the isocyanate content and it is 10.87%, which is lower than the theoretical value of 10.89%. Add 9g dimethyldipropylenetriamine and react at 60℃ for 1h. Test the isocyanate content and it is 5.63%, which is lower than the theoretical value of 5.64%. Cool to 40℃, add 26.25gSICO-A111 and react for 1.5h. Test the isocyanate content and it is 0.02%. Cool to below 20℃ and seal for storage.

[0104] Preparation of adhesive component A, the raw material ratio is as follows:

[0105] Table 7 Example 3 Component A Raw Material Ratio

[0106] raw material Brand or name Dosage (portion) Silane modified polyether M3001 62 Epoxy Curing Agent DMP-30 3 Modified crosslinking agent Modified crosslinking agent 7 Coupling agent Z6040 3 Additives U-5068 1.5 filler R202 4 Dewatering agent A171 1.5

[0107] Process steps: same as Example 1

[0108] Preparation of adhesive component B, the raw material ratio is as follows:

[0109] Table 8 Example 3 Component B Raw Material Ratio

[0110] raw material Brand or name Dosage (portion) Epoxy resin E51 91 filler R202 3 catalyst KAT245 3.5

[0111] Example 5

[0112] Preparation of modified crosslinking agent:

[0113] Put 20g IPDI, 25g HDI and 60g C2010 in a four-necked flask, add 0.02g bismuth neodecanoate as catalyst, react at 65℃ for 2h, test the isocyanate content and it is 13.19%, which is lower than the theoretical value of 13.21%. Add 13.8g N'N-bis(3-aminopropyl)methylamine and react at 60℃ for 1h. Test the isocyanate content and it is 4.89%, which is lower than the theoretical value of 4.95%. Cool to 40℃, add 31.05g KH550 and react for 1.5h. Test the isocyanate content and it is 0.02%. Cool to below 20℃ and seal for storage.

[0114] Preparation of adhesive component A, the raw material ratio is as follows:

[0115] Table 9 Example 3 Component A Raw Material Ratio

[0116] raw material Brand or name Dosage (portion) Silane modified polyether M3001 75 Epoxy Curing Agent DMP-30 5 Modified crosslinking agent Modified crosslinking agent 13 Coupling agent Z6040 1.5 Additives U-5068 2.5 filler R202 5 Dewatering agent A171 1.8

[0117] Process steps: same as Example 1

[0118] Preparation of adhesive component B, the raw material ratio is as follows:

[0119] Table 10 Example 3 Component B Raw Material Ratio

[0120] raw material Brand or name Dosage (portion) Epoxy resin E51 92 filler R202 2 catalyst KAT245 4

[0121] Comparative Example 1

[0122] Compared with Example 1, the modified crosslinking agent prepared by the modified crosslinking agent preparation method shown in the present invention is not contained.

[0123] Preparation of adhesive component A, the raw material ratio is as follows:

[0124] Table 11 Comparative Example 1 Component A Raw Material Ratio

[0125]

[0126]

[0127] Process steps: same as Example 1

[0128] Preparation of adhesive component B, the raw material ratio is as follows:

[0129] Table 12 Comparative Example 1 Component B Raw Material Ratio

[0130] raw material Brand or name Dosage (portion) Epoxy resin E51 93 filler R202 2.5 catalyst KAT245 2.5

[0131] Process steps: same as Example 1

[0132] Comparative Example 2

[0133] The crosslinking agent prepared by the modified crosslinking agent of the present invention reduces the amount of

[0134] Preparation of modified crosslinking agent: same as Example 1

[0135] Preparation of adhesive component A, the raw material ratio is as follows:

[0136] Table 13 Comparative Example 2 Component A Raw Material Ratio

[0137] raw material Brand or name Dosage (portion) Silane modified polyether M3001 58 Epoxy Curing Agent DMP-30 10 Modified crosslinking agent Modified crosslinking agent 2 Coupling agent Z6040 4 Additives U-5068 3 filler R202 10 Dewatering agent A171 2

[0138] Process steps: same as Example 1

[0139] Preparation of adhesive component B, the raw material ratio is as follows:

[0140] Table 14 Comparative Example 2 Component B Raw Material Ratio

[0141] raw material Brand or name Dosage (portion) Epoxy resin E51 90 filler R202 5 catalyst KAT245 5

[0142] Process steps: same as Example 1

[0143] Comparative Example 3

[0144] Compared with Example 1, the modified crosslinking agent is prepared without polyamine containing tertiary amine groups, and a small molecule alcohol is used as a chain extender.

[0145] Preparation of modified crosslinking agent:

[0146] Put 63gHMDI and 52gC2010D in a four-necked flask, add 0.02g bismuth neodecanoate as catalyst, react at 65℃ for 2h, test the isocyanate content and it is 9.22%, which is lower than the theoretical value of 9.25%. Add 5gBDO and react at 60℃ for 1h, test the isocyanate content and it is 5.15%, which is lower than the theoretical value of 5.18%. Cool down to 40℃, add 34.44gKH550 and react for 1.5h. Test the isocyanate content and it is 0.02%. Cool down to below 20℃ and seal for storage.

[0147] Preparation of adhesive component A, the raw material ratio is as follows:

[0148] Table 15 Comparative Example 3 Component A Raw Material Ratio

[0149] raw material Brand or name Dosage (portion) Silane modified polyether M3001 87 Epoxy Curing Agent DMP-30 2 Modified crosslinking agent Modified crosslinking agent 5 Coupling agent Z6040 1 Additives U-5068 1 filler R202 3 Dewatering agent A171 1

[0150] Process steps: same as Example 1

[0151] Preparation of adhesive component B, the raw material ratio is as follows:

[0152] Table 16 Comparative Example 3 Component B Raw Material Ratio

[0153] raw material Brand or name Dosage (portion) Epoxy resin E51 95 filler R202 1 catalyst KAT245 1

[0154] Process steps: same as Example 1

[0155] The above detection method was used to perform performance tests on the samples prepared in each embodiment and comparative example, and the elongation at break and the breaking strength of the body were tested. The test results of the shear strength of the samples of different substrates under normal conditions and after aging are shown in Table 18.

[0156] Table 18 Performance test results of samples

[0157]

[0158] The curing speed of each embodiment and comparative example was tested, and the results are shown in Table 19.

[0159] Table 19 Curing speed test

[0160]

[0161]

[0162] The shear strength of different substrates of each embodiment and comparative example was tested under conditions A-25°C, 50% RH for 7 days, condition B-5°C, 30% RH for 7 days, and condition C-40°C, 70% RH for 7 days. The results are shown in Table 20:

[0163] Table 20 Shear test of different substrates under different conditions

[0164]

[0165] It can be seen from the test results of Examples 1 to 5 and the comparative example that the adhesive prepared by the method provided by the present invention has good elongation at break and high bonding strength, is not strongly dependent on the use environment, has good consistency in cured bonding strength under different temperature and humidity conditions, does not require a primer, has good adhesion to a variety of materials such as conventional metals, engineering construction profiles, thermoplastic materials, glass, etc., has moderate viscosity, is anti-sagging, and has fast strength building. It exhibits good anti-aging properties under a variety of harsh conditions such as high temperature and high humidity, does not contain solvents, does not contain environmentally restricted components such as butyl tin, octyl tin, and phenyl tin, and meets environmental protection requirements.

[0166] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the spirit of the present invention.

Claims

1. A two-component adhesive, the adhesive consisting of component A and component B; The A component comprises the following components in parts by weight: The B component includes the following components in parts by weight: Epoxy resin 90-95 parts Filler 1-5 parts Catalyst 1-5 parts The mixing mass ratio of component A to component B is 1:1 to 3:

1.

2. The two-component adhesive according to claim 1, characterized in that The silane-modified polyether in the A component is a dimethoxy-terminated silane-modified polyether and a trimethoxy-terminated silane-modified polyether, such as one or more of SAX750, SAX260, SAX590, Wacker Chemical E35, Wacker Chemical E10, Ruiyang Antai 350A, and Xinda Chemical M3001.

3. The two-component adhesive according to claim 1 or 2, characterized in that: The epoxy curing agent in component A is selected from at least one of aliphatic amines, aromatic amines, aliphatic rings, modified amines, tertiary amines, acid anhydrides, low molecular weight polyamides and latent amines, for example, one or more of (1,3-cyclohexanedimethylamine) alicyclic amine, diethylenetriamine, isophoronediamine, 2,4,6-tris(dimethylaminomethyl)phenol and benzyldimethylamine.

4. The two-component adhesive according to any one of claims 1 to 3, characterized in that: The preparation method of the modified cross-linking agent comprises the following steps: Place isocyanate and polyol in a reactor, add a catalyst and react at 65-75°C for 2-3 hours, test the isocyanate content of the reaction, when the isocyanate content reaches the theoretical value, add an alcohol or amine containing a tertiary amine group and react at 60-65°C for 1-2 hours, when the isocyanate content reaches the theoretical value, cool to 30-40°C, add monoaminosiloxane and react for 1-2 hours, when the isocyanate content reaches the theoretical value, cool to obtain a modified cross-linking agent.

5. The two-component adhesive according to claim 4, characterized in that The isocyanate is selected from one or more of diphenylmethane diisocyanate, hexamethylene diisocyanate, dicyclohexylmethane diisocyanate, and isophorone diisocyanate; and / or the polyol is polypropylene oxide alcohol and / or polyethylene oxide alcohol; for example, polypropylene oxide diol or triol and / or polyethylene oxide diol or triol alcohol having a number average molecular weight of 400-1000, selected from one or more of Wanhua Chemical C2004, C2010D, C2010A, R2303, and R2304; and / or the alcohol or amine containing a tertiary amine group is one or more of N-methyldiethanolamine, dimethyldipropylenetriamine, and N,N-bis(3-aminopropyl)methylamine.

6. The two-component adhesive according to claim 4 or 5, characterized in that: The monoaminosiloxane is one or more of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, and 3-aminopropylmethyldiethoxysilane; and / or the catalyst is bismuth neodecanoate or zinc isooctanoate; and / or the mass ratio of the isocyanate, the polyol, the alcohol or amine containing a tertiary amine group, and the monoaminosiloxane is (45-70): (40-55): (9-14): (25-37).

7. The two-component adhesive according to any one of claims 1 to 6, characterized in that: The coupling agent is at least one of an amine-containing coupling agent and an epoxy-containing coupling agent, such as 3-aminopropyltriethoxysilane KH550, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane KH792, and 3-(2,3-epoxypropoxy)propyltrimethoxysilane Z6040; and / or the dehydrating agent is a vinyl silane, such as at least one of vinyltrimethoxysilane, vinyltriethoxysilane, and vinyltri(methoxyethoxy)silane.

8. The two-component adhesive according to any one of claims 1 to 7, characterized in that: The auxiliary agent is one or more of an ultraviolet absorber, a hindered amine light stabilizer and an antioxidant with a light stabilizing effect, such as Tinuvin B75 and Tinuvin B88 produced by BASF of Germany, and Shanghai Puzhan U5068; and / or, the epoxy resin is a bisphenol A type epoxy resin, such as Baling Petrochemical Epoxy Resin E51 and E44.

9. A method for preparing a two-component adhesive as claimed in any one of claims 1 to 8, comprising the following steps: (1) Preparation of component A: silane-modified polyether and filler are mixed and dehydrated at 90-120° C. and vacuum degree of -0.06 to -0.1 MPa for 1-2 h, cooled to below 30° C., epoxy curing agent, modified cross-linking agent, coupling agent, auxiliary agent, and dehydrating agent are added, and stirred at vacuum degree of -0.06 to -0.1 MPa for 0.5 to 1 h to obtain component A; (2) Preparation of component B: The modified epoxy resin and filler are mixed and dehydrated at 90 to 120° C. and a vacuum degree of -0.06 to -0.1 MPa for 1 to 2 hours, the temperature is lowered to below 30° C., a catalyst is added, and the mixture is stirred at a vacuum degree of -0.06 to -0.1 MPa for 0.5 to 1 hour to obtain component B; (3) Mix component A and component B in a ratio of 1:1 to 3:

1. Use of the two-component adhesive as described in any one of claims 1 to 8 or the two-component adhesive prepared by the preparation method as described in claim 9 in bonding materials, wherein the bonding materials include aluminum, stainless steel, galvanized sheet, glass, PVC, PC, ABS, etc.

Citation Information

Patent Citations

  • Silane modified polyurethane-epoxy composition and preparation method thereof

    CN111635729A

  • Bi-component modified epoxy adhesive for bonding passenger car skin and preparation method of bi-component modified epoxy adhesive

    CN115746769A

  • Bi-component silane modified polyether type three-proofing glue and preparation method thereof

    CN115926719A

  • Epoxy resin-silane-terminated resin two-component hybrid structural adhesive as well as preparation method and application thereof

    CN117126633A

  • Silane-terminated polymer-based adhesive as well as preparation method and application thereof

    CN117887400A